ABILITY TO APPLY THE ACHIEVEMENTS OF MODERN SCIENCE IN PRACTICE, CREATIVE APPROACH TO PROBLEM SOLVING - Tanjarova Rano Akramovna (Journals Park Publishing, 2023)
This article is about the ability to apply the achievements of modern science in practice, creative approach to problem solving. Based on scientific data and written sources, the author studied the existing specific aspects of the subject, clarified the problem on the basis of existing literature.
Keywords: Modern, science, achievements, innovation, development, technique, technology.